Effects of maleic anhydride on hydroxyapatite powder filled PP composites properties - (:unkn) unknown (Metal Powder Industries Federation, 2017)
In this investigation, composites of polypropylene, synthetic hydroxyapatite and maleic anhydride powder were prepared. The effects of synthetic hydroxyapatite and maleic anhydride powder ratio on the mechanical and morphological properties of the polymer composites is presented. Synthetic hydroxyapatite powder (30 wt %) was added to PP to produce composites. Maleic anhydride powder, in four different concentrations (1, 5, 10 and 15 wt %), were added to PP to produce composites as well. The mechanical properties, including the elastic modulus, yields strengths, tensile strengths, strain at tensile strength, Izod impact resistance, hardness, density of the composites were investigated. The structure of the composites were investigated by scanning electron microscopy and compared to mechanical and thermal properties as a function of hydroxyapatite and maleic anhydride powder content. © 2017 Metal Powder Industries Federation. All Rights Reserved.